Predation and spatial connectivity interact to shape ecosystem resilience to an ongoing regime shift - Agnes B. Olin; Ulf Bergström; Örjan Bodin; Göran Sundblad; Britas Klemens Eriksson; Mårten Erlandsson; Ronny Fredriksson; Johan S. Eklöf (Nature Communications, 2024)
Abstract Ecosystem regime shifts can have severe ecological and economic consequences, making it a top priority to understand how to make systems more resilient. Theory predicts that spatial connectivity and the local environment interact to shape resilience, but empirical studies are scarce. Here, we use >7000 fish samplings from the Baltic Sea coast to test this prediction in an ongoing, spatially propagating shift in dominance from predatory fish to an opportunistic mesopredator, with cascading effects throughout the food web. After controlling for the influence of other drivers (including increasing mesopredator densities), we find that predatory fish habitat connectivity increases resilience to the shift, but only when densities of fish-eating top predators (seals, cormorants) are low. Resilience also increases with temperature, likely through boosted predatory fish growth and recruitment. These findings confirm theoretical predictions that spatial connectivity and the local environment can together shape resilience to regime shifts.